2018
DOI: 10.1016/j.molcel.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Discovery of RNA Binding Proteins that Regulate MicroRNA Levels

Abstract: RNA binding proteins (RBPs) interact with primary, precursor, and mature microRNAs (miRs) to influence mature miR levels, which in turn affect critical aspects of human development and disease. To understand how RBPs contribute to miR biogenesis, we analyzed human enhanced UV crosslinking followed by immunoprecipitation (eCLIP) datasets for 126 RBPs to discover miR-encoding genomic loci that are statistically enriched for RBP binding. We find that 92% of RBPs interact directly with at least one miR locus, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
106
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 41 publications
8
106
1
Order By: Relevance
“…The ENCODE RNA binding protein resource contains 1,223 replicated datasets for 356 RBPs, including in vivo targets by eCLIP, in vitro binding motifs by RNA Bind-N-Seq, subcellular localization by immunofluorescence, factor-responsive expression and splicing changes by knockdown/RNA-seq, and DNA associations by ChIP-seq [20]. This unique resource has already proven useful in characterizing allele-specific RBP interactions [51,52], identify candidate regulators of miRNA processing [53], predicting whether RNAs are protein-coding or non-coding [54], and identifying novel factors which act to suppress improper RNA processing caused by retrotransposable elements [36], and will continue to enable researchers to ask broad questions about basic RNA processing mechanisms, deeply consider the functional roles of an individual RBP, or even query an RNA of interest in order to gain insight into potential regulators. Here we describe examples how integrated analyses of binding profiles obtained from eCLIP can yield novel insights into both processing of standard mRNAs as well as other RNA families, including identifying new characteristics of ribosomal RNA processing and the role of RBP interactions with retrotransposable elements.…”
Section: Discussionmentioning
confidence: 99%
“…The ENCODE RNA binding protein resource contains 1,223 replicated datasets for 356 RBPs, including in vivo targets by eCLIP, in vitro binding motifs by RNA Bind-N-Seq, subcellular localization by immunofluorescence, factor-responsive expression and splicing changes by knockdown/RNA-seq, and DNA associations by ChIP-seq [20]. This unique resource has already proven useful in characterizing allele-specific RBP interactions [51,52], identify candidate regulators of miRNA processing [53], predicting whether RNAs are protein-coding or non-coding [54], and identifying novel factors which act to suppress improper RNA processing caused by retrotransposable elements [36], and will continue to enable researchers to ask broad questions about basic RNA processing mechanisms, deeply consider the functional roles of an individual RBP, or even query an RNA of interest in order to gain insight into potential regulators. Here we describe examples how integrated analyses of binding profiles obtained from eCLIP can yield novel insights into both processing of standard mRNAs as well as other RNA families, including identifying new characteristics of ribosomal RNA processing and the role of RBP interactions with retrotransposable elements.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely facilitated by the recruitment of functionally-related miRNAs into specific miRNA-RBP ternary complexes (e.g. TUG1-hnRNPA1-SET/CCND2/CDK6) 59,61,74 . In this regard, we showed that 15 validated TUG1-interacting miRNAs are differentially expressed in CD34 + CD38and CD34 + CD38 + CML (CP and BC) BM cells and have defined roles in solid tumors and AML/CML stem/progenitor cells 75 (Supplementary Fig.…”
Section: Biologic and Therapeutic Relevance Of The Mir300-tug1 Interpmentioning
confidence: 99%
“…Notably, not all human pri-miRNAs contain such motifs, suggesting that other factors may enable Microprocessor-mediated processing. Indeed, various accessory proteins have been reported to either bind directly to the pri-miRNA or to the Microprocessor itself , thereby assisting in pri-miRNA cleavage (Alarcón et al, 2015;Cheng et al, 2014;Fletcher et al, 2016;Nussbacher and Yeo, 2018;Treiber et al, 2017;Tu et al, 2015). Moreover, recent studies also reveal stem-loop structures as cis-regulatory elements in pri-miRNA processing.…”
Section: Introductionmentioning
confidence: 99%